Pengaruh Video Kartun Diva terhadap Kemampuan Literasi Membaca di TK Perwati Kecamatan Kota Tengah Kota Gorontalo - Sri Gina Fitri Arianto; Pupung Puspa Ardini; Rapi Us. Djuko (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This study aims to examine the influence of Diva cartoon videos on reading literacy skills at TK Perwati Kindergarten, Kota Tengah District, Gorontalo City. The researcher used quantitative research with an experimental method, specifically a pre-experimental design in the form of a one-group pre-test and post-test design. The study results, with a sample size of 16 children, showed a difference in the average scores between the pre-test and post-test, which were 13.69 and 29.13, respectively. Furthermore, the hypothesis testing indicated that the hypothesis (Hi) was accepted, with a linear regression test showing a significant value of 0.000, which was less than 0.05. This proves that Diva cartoon videos significantly affect children's reading literacy skills at TK Perwati Kindergarten, Kota Tengah District, Gorontalo City.